2007
DOI: 10.1080/09640560601156466
|View full text |Cite
|
Sign up to set email alerts
|

Green exercise in the UK countryside: Effects on health and psychological well-being, and implications for policy and planning

Abstract: There is evidence that contact with the natural environment and green space promotes good health. It is also well known that participation in regular physical activity generates physical and psychological health benefits. The authors have hypothesised that 'green exercise' will improve health and psychological well-being, yet few studies have quantified these effects. This study measured the effects of 10 green exercise case studies (including walking, cycling, horse-riding, fishing, canal-boating and conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
320
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(358 citation statements)
references
References 24 publications
13
320
2
6
Order By: Relevance
“…Additionally, some of the heritage activities included in the category involve the outdoors which might act in combination with physical activity to improve mental health and, indirectly, life satisfaction (Bodin and Hartig 2003;Pretty et al 2005;Pretty et al 2007;Thompson Coo et al 2011;Mitchell 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some of the heritage activities included in the category involve the outdoors which might act in combination with physical activity to improve mental health and, indirectly, life satisfaction (Bodin and Hartig 2003;Pretty et al 2005;Pretty et al 2007;Thompson Coo et al 2011;Mitchell 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a public consultation carried out by Oxfam, access to arts, culture, hobbies and leisure activities emerged unprompted as an important "sub-domain" of wellbeing and indeed seen as a flourishing aspect (Walker et al 2012). Research on leisure and wellbeing tends to concentrate in the area of physical activity, in general or carried out in outdoor environments, and its association with psychological wellbeing (Dowall et al 1988;Foong 1992;Bodin and Hartig 2003;Wendel-Vos et al 2004;Pretty et al 2005;Pretty et al 2007;Hug et al 2009;Thompson Coon et al 2011;Mitchell 2012). However, not many studies have compared different types of leisure activities, including arts and culture, in relation to their contribution to life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Communal green spaces in urban areas have been linked to higher levels of community cohesion and social interaction among neighbors (Kuo and Sullivan 2001). Pretty et al (2007) demonstrated the impact of access to green space on both physiological and psychological well-being.…”
Section: Components Of Human Well-beingmentioning
confidence: 99%
“…This disorder has stimulated legislative (No Child Left Inside Act of 2009) grassroots community efforts, 1 and ''right of bills'' types of manifestos. Interactions with nature and its ecosystem services have been shown to enhance cognitive and problem-solving abilities, promote independence, focus attention, promote better environmental awareness, generally benefit early childhood development (Cohn and Horm-Wingerd 1993;Kahn and Kellert 2002;Moore et al 2004;Louv 2005;van Noy 2008); and even, reduce obesity by reducing time spent interacting with stationary media like television and video games (Kaiser Family Foundation 2005) or increasing exercise times (Pretty et al 2007). Natural interactions with ecosystems have been shown to have enhanced educational benefits through wilderness interactions for inner city youth (Faber Taylor et al 2001b), improved educational skills and enhanced educational and developmental skills (Lieberman and Hoody 1998).…”
Section: Basic Human Needsmentioning
confidence: 99%
“…In one of their earliest works, images of nature or built environment were displayed on a screen whilst the subjects exercised on a treadmill, showing that watching images of pleasant natural environment while exercising elicited improvements of mood profiles and greater reduction in blood pressure (Pretty, Peacock, Sellens, & Griffin, 2005). In other studies in the field, it was shown that green exercise experiences were associated with greater positive mental states, both in healthy (Barton & Pretty, 2010;Pretty et al, 2007) and clinical population (Brown, Barton, Pretty, & Gladwell, 2012).…”
Section: Physical Activity and Nature Eliciting Positive Mental Statesmentioning
confidence: 99%